Analysis of the Arabica Green Bean Coffee Production Process Using the Natural Anaerobic Method - Nuraini Azizah; Santosa Santosa; Neswati Neswati (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
The natural anaerobic method has become an innovative post-harvest processing technique that can improve the physical quality and market value of specialty Arabica coffee. This study aimed to analyze the production process, yield, and physical quality characteristics of Arabica green coffee processed using the natural anaerobic method at the Koerintji Barokah Bersama Cooperative in Kerinci Regency. The results showed that the total yield of green beans was 14.43%, with an average input of 308.33 kg of coffee cherries resulting in an output of 44.50kg. Based on the results of the sieve-based bean size test, most of the green beans were classified as medium in size, indicating a good level of bean size uniformity. The green beans produced have met SNI quality standards, indicated by the absence of live insects or odor defects. The average moisture content of 10.57%, the dirt content of 0.16%, and the bean defect value of 9.18 indicate that the coffee beans fall within quality category I. Overall, the natural anaerobic method produces Arabica green coffee beans with optimal yield, relatively uniform bean size, and good physical quality. Contribution to Sustainable Development Goals (SDGs):SDG 1: No PovertySDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 15: Life on Land